Probabilistik Kelongsoran Lereng Tambang Terbuka Grasberg PT Freeport Indonesia - Iswandaru Iswandaru; Rully Nurhasan R.; Made Astawa Rai; Ridho K. Wattimena (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2019)
The stability of a slope in mining activities is highly influenced by geology, especially thenature of rocks and geological structures. Slope stability analysis will be faced with severalproblems in the uncertainty of rock properties and rock mass. Slope stability analysis usingprobabilistic methods offers a more systematic way of treating conditions of uncertainty andprovides other alternatives to the value factor approach to security regarding information onthe probability of a slope failure.Grasberg Open Mine rock type classification based ongeotechnical parameters or Geotechnical Rock Code (GTRCK) classifies rocks based onrock type, rock mechanical properties, hydrothermal alteration type, clay content and RockQuality Designation (RQD) to 46 types of GTRCK. The GTRCK type which has a low rockmass strength value is a change in intrusive rock minerals and a low RQD value such as alot of clay material is exposed in the Northeast and Southwest of the Grasberg Open PitMine.The overall slope probabilistic modeling of the Grasberg mine uses a cross section of220o (northwest) with the effect of a 0.02g seismic factor which is the maximum criterionaccording to the probability of slope failure received with the average FK 1.13 and PK 0%.